Between the lines - Picoult, Jodi, 1966-; Leer, Samantha van.; Gilbert, Yvonne; Fischer, Scott M. (New York : Simon Pulse/Emily Bestler Books/Atria, 2012)
Told in their separate voices, sixteen-year-old Prince Oliver, who wants to break free of his fairy tale existence, and fifteen-year-old Delilah, a loner obsessed with Prince Oliver and the book in which he exists, work together to seek his freedom.
Keywords: Books and reading -- Fiction; Fairy tales -- Fiction; Princes -- Fiction; High schools -- Fiction; Schools -- Fiction; Mothers and daughters -- Fiction